A Multidisciplinary Approach in Treating a Patient with Unilateral Cleft Alveolus - Das, D (Kathmandu University Medical Journal, 2015)
Any type of aesthetic correction in dental practice is always a challenging task, especially when it is complicated with cleft lip and alveolus. Careful examination and correct decision making at early stage of treatment and multi disciplinary approach is always necessary for long term success. This paper described a multidisciplinary approach in managing a 19-year-old female patient with unilateral cleft alveolus impacted maxillary canine , missing lateral incisor and hypoplastic central incisor by surgical , orthodontic and prosthodontic means. The impacted canine was surgically exposed and orthodontic traction given to bring it into the normal alignment. The missing lateral incisor was replaced by a fixed bridge with a ceramic gingival fixed prosthesis to manage alveolar cleft. At the same time the hypoplastic defect of central incisor was hidden by the full coverage retainer used for the bridge abutment on the tooth. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12497 Kathmandu University Medical Journal Vol.11(2) 2013: 171-174